Psychometric characteristics of the Turkish version of the nurse comfort questionnaire - Çınar Yücel, Şebnem; Göke Arslan, Gamze; Ergin, Eda; Kuğuoğlu, Sema (Springer, 2019)
The aim of this study was to determine psychometric characteristics of the Turkish version of the Nurse Comfort Questionnaire (NCQ). The sample of the study comprised 275 nurses in the western part of Turkey. To collect the study data, the Sociodemographic Characteristics Questionnaire and NCQ were used. After the statistical analyses conducted to determine the validity and reliability of the Turkish version of the Ferrandiz and Martin-Baena’s NCQ, some items were excluded from the original questionnaire, and a 39-item NCQ for Turkey was developed. The analyses showed that the 39-item NCQ had a valid and reliable structure of Turkish nurses.
Keywords: Comfort Theory; Nurse Comfort Questionnaire; Nursing; Reliability; Validity